The Synthesis and Anti‐tumour Properties of Poly Ethoxy Ethyl Glycinamide (PEE−G) Scaffolds with Multiple PD‐1 Peptides Attached. (2nd June 2020) - Shrestha, Rinu; Petley, Emma V.; Farrand, Kathryn J.; Jamieson, Sam A.; Jiao, Wanting; Teesdale‐Spittle, Paul H.; Mace, Peter D.; Hermans, Ian F.; Rendle, Phillip M.
Abstract: Multivalent structures can provide multiple interactions at a target site and improve binding affinity. The multivalent presentation of the anti‐tumour heptapeptide, SNTSESF, was investigated. This peptide's activity has been attributed to blockade of the PD‐1 receptor‐mediated signalling pathway. Two and four peptide units were conjugated to poly ethoxy ethyl glycinamide (PEE−G) scaffolds to prepare high‐purity products. These conjugates and the peptide were examined in a mouse model implanted with GL261 tumours that indicated that presenting more than two copies of peptide SNTSESF on the dendritic scaffold does not increase anti‐tumour activity per peptide. The fluorescent labelled peptide and most active multivalent peptide conjugate were therefore screened for their interaction with the human PD−L1 protein in a fluorescence polarisation assay. No indication of a specific SNTSESF peptide/PD−L1 interaction was observed. This finding was further supported by a molecular modelling binding study. Abstract : Mode of action ? Copies of a peptide fragment (SNTSESF) of the programmed death‐1 protein (PD‐1) with known anti‐tumour activity were conjugated to poly ethoxy ethyl glycinamide (PEE−G) scaffolds. Scaffolds with two and four peptide units were examined in a mouse tumour model. Molecular modelling and fluorescence polarisation assay were used to examine the interaction of the peptide with PD‐1 ligands.